(untitled) (Bangladesh Critical Care Journal, 2024)
Acute pancreatitis is a painful condition in which the pancreas becomes inflamed and edematous usually for a short period of time. Pulmonary embolism due to severe acute pancreatitis is a rare but serious condition. A 68-year-old patient got admitted in gastroenterology department of a tertiary care hospital of Dhaka, Bangladesh with chief complaints of severe abdominal pain for 5 hours and several episodes of vomiting for same duration. After admission relative investigation and examination were done. His USG revealed swollen oedematous pancreas with peripancreatic fluid collection, bilateral renal parenchyma changes with cortical cyst. Patient’s Glasgow Imrie score was 3, Numeric pain score (NRS) was 4, Urine output was normal. The patient was categorized into severe acute pancreatitis. The patient was treated with antimicrobials, proton pump inhibitors, analgesic, and fluid resuscitation. But patient’s medical condition deteriorated and oxygen demand increased. Due to susceptibility of pulmonary embolism and worsening of patient’s condition a thrombolysis was done. Severe acute pancreatitis complicating with pulmonary embolism is a fatal condition.1 Early diagnosis and treatment are fundamental for treating this dreadful condition. When Patient with acute pancreatitis exhibits dyspnoea, leg oedema and thromboembolic events, pulmonary embolism should be suspected. Following early diagnosis, thrombolysis is necessary to combat this situation. Bangladesh Crit Care J March 2024; 12 (1): 50-54